PENGELOLAAN LIMBAH PADAT KOTA PALU BERDASARKAN BIAYA PENGELOLAAN OPTIMAL - Pratamasyari, D A (Program Studi Matematika, Universitas Tadulako, 2019)
Waste is one of the source environmental problem point problem that need to attention. Waste problem becomes complex to be solved because related to the waste. In this research, waste management in Palu City is assessed based on optimal costs. real waste management in Palu City which is managed conventionally. Research result shows that the waste management of Palu city can be derived into such optimal, with the models of mathematic is to minimize which to have 3 constraint. The riil cost for manage Palu city is Rp.8.050.330.000. Keywords : waste management , mathematical models , optimal